A Comparison by Gender: Interest and Science Process Skills - Budiarti, Retni Sulistiyoning; Kurniawan, Dwi Agus; Rohana, Siti (Journal of Education Reseach and Evaluation, 2022)
This learning skill is a thing that supports the implementation of a good learning process. Monotonous learning will be difficult to accept, this causes students to be lazy to do assignments because of the applied education system. This study aims to analyze the comparison of interest and science processes and to determine the relationship between students' interest and science process skills between women and men in science subjects. The method in this research is comparative quantitative data analysis. Where comparative is research that compares two or more variables. The results of this study are the t-test of students' science process skills on science lessons for both female and male students, so it can be concluded that there is a relationship between the science process skills of class VII A and class VII B students. Class VII A and class VII B students. Science process skills In science subjects for class VII A, it can be concluded that there is a relationship between interest and science process skills between female and male students as well as in grades VII A and B. This research is very important to do because there are not many studies that compare the interests and skills of the science process with several tests that are used. It is very useful to know about the comparison of interests and skills of the science process in each class and the comparison of indicators that will be used.